Black tea and improvement of attention: evaluation of a health claim pursuant to Article 13(5) of Regulation (EC) No 1924/2006. (24th May 2018) - ,; Turck, Dominique; Bresson, Jean‐Louis; Burlingame, Barbara; Dean, Tara; Fairweather‐Tait, Susan; Heinonen, Marina; Hirsch‐Ernst, Karen Ildico; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Neuhäuser‐Berthold, Monika; et al.
Abstract: Following an application from Unilever NV, submitted for authorisation of a health claim pursuant to Article 13(5) of Regulation (EC) No 1924/2006 via the Competent Authority of Ireland, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver an opinion on the scientific substantiation of a health claim related to black tea and improvement of attention. The scope of the application was proposed to fall under a health claim based on newly developed scientific evidence. The food proposed by the applicant as the subject of the health claim is black tea. The Panel considers that black tea characterised by its content of tea solids, caffeine and l ‐theanine, which is the subject of the health claim, is sufficiently characterised in relation to the claimed effect. The claimed effect proposed by the applicant is 'improves attention'. The Panel considers that improvement of attention is a beneficial physiological effect. Three human intervention studies provided by the applicant show an effect of black tea on attention under the conditions of used proposed by the applicant. The applicant proposed that the claimed effect depends on the concerted action of two substances, caffeine and l ‐theanine, both of which are present in black tea. The Panel considers that the effect of black tea on attention observed in the three human intervention studies provided by the applicant can be explained by its caffeine content. The Panel concludes that a cause and effect relationship has been established between the consumption of black tea and improvement of attention. The Panel considers that the effect of black tea on attention can be explained by its caffeine content. The following wording reflects the scientific evidence: 'Owing to its caffeine content, black tea improves attention'. In order to obtain the claimed effect, 2–3 servings of black tea providing at least 75 mg of caffeine in total should be consumed within 90 min.